A sustainable solar-driven electrochemical process for reforming lignocellulosic biomass effluent into high value-added products: green hydrogen, carboxylic and vanillic acids - Campos da Paixão, Izaías; Cardozo, Jussara Câmara; Sales Monteiro, Mayra Kerolly; Gondim, Amanda Duarte; Cavalcanti, Lívia Nunes; Fabiano de Santana Souza, Domingos; Martínez-Huitle, Carlos A. [UNESP]; Vieira dos Santos, Elisama [UNESP] (Royal Society of Chemistry (RSC), 2023)
There is a growing concern with waste minimization and the promotion of the circular economy. Within this framework, using membrane-equipped electrochemical systems, the electrochemical oxidation (EO) of organic compounds and simultaneous hydrogen (H2) production can considerably improve the sustainability and economic viability of this process. Here, we propose an innovative-integrate electrochemical treatment strategy to maximize the economic benefits and sustainability of selectively producing organic acids and energy-saving H2 production from biomass platform compounds. The results clearly demonstrated that, on the one hand, more than 80 mg L−1 of oxalic acid was obtained in the anodic reservoir (using a boron-doped diamond electrode) with an alkaline medium (0.5 mol L−1 NaOH) by applying 100 mA cm−2 as well as vanillic acid production of 0.6795 mg L−1 under the same conditions. On the other hand, simultaneously green H2 production greater than 2.6 L was produced, in the cathodic compartment with a Ni-Fe-based mesh as cathode, with a 90% faradaic efficiency during the process. Thus, the electrochemical conversion of lignocellulosic biomass effluent into high-value-added products and an energy vector was sustainably accomplished, suggesting that it is a promising energy-saving and cost-effective integrated approach for biomass valorization using solar energy.